2021
DOI: 10.20473/jovin.v2i1.26179
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kegel Exercise on the Quality of Life in Post Turp Patients at Muhammadiyah Hospital

Abstract: Introduction: Urinary incontinence is a comorbid condition that often occurs in post TURP clients. Low urinary incontinence scores were found in post TURP clients who did Kegel exercises. The purpose of this study was to explain the effect of Kegel exercise on urinary incontinence, and quality of life in post- TURP clients. Methods: The study design was a true experiment pre-post test control group design. The sample size was 32 people who were selected by systematic random sampling, consisting of 16 people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previous studies and systematic reviews have shown that performing Kegel exercise after TURP can effectively improve urinary incontinence. [25][26][27][28] Older patients may question whether performing Kegel exercises will increase postoperative prostate bleeding or other problems. Most cases of postoperative bleeding may be associated with excessive physical exertion, such as climbing stairs, sexual intercourse, and constipation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies and systematic reviews have shown that performing Kegel exercise after TURP can effectively improve urinary incontinence. [25][26][27][28] Older patients may question whether performing Kegel exercises will increase postoperative prostate bleeding or other problems. Most cases of postoperative bleeding may be associated with excessive physical exertion, such as climbing stairs, sexual intercourse, and constipation.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the patients performed the Kegel exercise because they did not experience stress urinary incontinence after TURP. Previous studies and systematic reviews have shown that performing Kegel exercise after TURP can effectively improve urinary incontinence 25–28 . Older patients may question whether performing Kegel exercises will increase postoperative prostate bleeding or other problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACO approach is used to optimize the weights of neural networks because the BP method might become stuck in a local optimum when applied to large datasets. In order to increase the performance of an ACO training network, it is necessary to use the better weight as the starting point for further optimization using the BP technique [9]. After conducting a thorough examination, Efat et al came to the conclusion that the application of artificial intelligence and expert system design concepts could be beneficial to doctors in the future [10].…”
Section: Introductionmentioning
confidence: 99%